2015
DOI: 10.1126/scitranslmed.aab3964
|View full text |Cite
|
Sign up to set email alerts
|

Quality and quantity of T FH cells are critical for broad antibody development in SHIV AD8 infection

Abstract: Broadly neutralizing antibodies (bNAbs) protect against HIV-1 infection, yet how they are generated during chronic infection remains unclear. It is known that T follicular helper (TFH) cells are needed to promote affinity maturation of B cells during an immune response; however, the role of TFH during HIV-1 infection is undefined within lymph node germinal centers (GCs). We use nonhuman primates to investigate the relationship in the early stage of chronic SHIVAD8 (simian-human immunodeficiency virus AD8) infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
129
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 55 publications
4
129
0
Order By: Relevance
“…Notably, none of these studies examined HIV-specific CD4 ϩ T cells. However, an eloquent study by Yamamoto et al recently reported that the quantity and quality of Env-specific germinal center (GC) Tfh cells were associated with broader antibody neutralization in SHIV-infected macaques (6). These authors found that IL-4-producing Env-specific GC Tfh cells were associated with an expansion of Env-specific immunoglobulin G-positive GC B cells, and using cluster analysis they identified 13 variables, including the percentage of Env-and Gagspecific CD154…”
Section: Fig 7 the Magnitude Of Gag-specific Cd4mentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, none of these studies examined HIV-specific CD4 ϩ T cells. However, an eloquent study by Yamamoto et al recently reported that the quantity and quality of Env-specific germinal center (GC) Tfh cells were associated with broader antibody neutralization in SHIV-infected macaques (6). These authors found that IL-4-producing Env-specific GC Tfh cells were associated with an expansion of Env-specific immunoglobulin G-positive GC B cells, and using cluster analysis they identified 13 variables, including the percentage of Env-and Gagspecific CD154…”
Section: Fig 7 the Magnitude Of Gag-specific Cd4mentioning
confidence: 99%
“…Additionally, we calculated the antibody neutralization score to quantify the breadth and potency of plasma neutralization activity per patient. Points were assigned based on the ID 50 titers for each of the 11 tier 2/3 viruses: one point was awarded for titers up to 99, two points were given for titers of 100 to 999, and three points were awarded for titers greater than 1,000 ID 50 s, as described previously (6). The points were then summed to provide the overall neutralization score per patient.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, bnAbs against HIV-1 tier 2 isolates have rarely been detected in SHIV-infected macaques (5)(6)(7)(8)(9). A previous screening of 40 macaques infected with uncloned SHIV AD8 or a molecular clone of SHIV AD8-CK15 identified a single animal, CE8J, that developed potent bnAbs directed to the N332 glycosylation site (5).…”
mentioning
confidence: 99%